2004
DOI: 10.1111/j.1365-2141.2004.04893.x
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant bispecific single‐chain Fv antibody against HLA class II and FcγRIII (CD16) triggers effective lysis of lymphoma cells

Abstract: Summary Bispecific antibodies offer the possibility of improving effector‐cell recruitment for antibody therapy. For this purpose, a recombinant bispecific single‐chain Fv antibody (bsscFv), directed against FcγRIII (CD16) and human leucocyte antigen (HLA) class II, was constructed and tested in functional assays. RNA from the hybridomas 3G8 and F3.3, reacting with CD16 and HLA class II, respectively, was used to generate phage display libraries. From these libraries, reactive phages were isolated and the bssc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…To analyze binding of B7-H6:7D8 and B7-H6:4D5, Ramos or MDA-MB-361 cells were incubated with either protein on ice for 45 min, then washed with 2 ml PBA buffer and subsequently stained with a secondary Alexa Fluor 488-coupled anti-penta His Ab (Qiagen) on ice for 30 min. To determine the affinity of B7-H6:7D8 for CD20, binding curves were recorded and equilibrium constants (K D values) were calculated as described (31). To demonstrate simultaneous binding, Ramos cells were preincubated with B7-H6:7D8 (ULBP2:7D8 as negative control) at 50 mg/ml followed by the fusion protein NKp30-Fc ko at 100 mg/ml.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze binding of B7-H6:7D8 and B7-H6:4D5, Ramos or MDA-MB-361 cells were incubated with either protein on ice for 45 min, then washed with 2 ml PBA buffer and subsequently stained with a secondary Alexa Fluor 488-coupled anti-penta His Ab (Qiagen) on ice for 30 min. To determine the affinity of B7-H6:7D8 for CD20, binding curves were recorded and equilibrium constants (K D values) were calculated as described (31). To demonstrate simultaneous binding, Ramos cells were preincubated with B7-H6:7D8 (ULBP2:7D8 as negative control) at 50 mg/ml followed by the fusion protein NKp30-Fc ko at 100 mg/ml.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Single clones were isolated by limiting dilution. The Histagged proteins were purified by affinity chromatography with Ni-NTA agarose beads (Qiagen, Hilden, Germany) as described (31). Fc containing fusion proteins were purified as described (28).…”
Section: Expression and Purificationmentioning
confidence: 99%
“…Thereby the vector pSecTag2HygroC-STREP-His-CD123 · dsCD16 · CD33 was produced. In these constructs, the index ds designates the disulfide-stabilized variants (Bruenke et al, 2004). To generate the vector pSecTag2HygroC-STREP-His-CD123 · dsCD16 · CD123, the sequence coding for the CD123-specific scFv was amplified by polymerase chain reaction (PCR) from the vector pAK400-CD123scFv and ligated into pSecTag2-HygroC-STREP-His-CD123 · dsCD16 · CD33, using XhoI/ EcoRV restriction sites, and replacing the coding sequence for the C-terminal CD33-specific scFv.…”
Section: Construction Of Sctbs [123mentioning
confidence: 99%
“…As for lymphoma, so far only two studies have reported the generation of specific phage display library. Bruenke et al [22] generated bispecific single-chain Fv antibody (bsscFv) from hybridomas 3G8 and F3.3 using the phage display library, which could mediate specific lysis of malignant human B-lymphoid cell lines. In another report, Dong et al [23] isolated two Fab clones against the viral capsid antigen (VCA) of Epstein-Barr virus (EBV) from a patient with marginal zone B cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%